Current Status of Conservation and Exploitation of Unique Values of Typical Folk Art Forms in Tourism Development in Ethnic Minorities in Ha Giang Province, Vietnam - Vien, VU Van; Tam, NGUYEN Thi; Son, QUANG Van; Huyen, DO Thi Thu (Journal of Ecohumanism, 2024)
Ha Giang is a province in the northeastern region of Vietnam, adjacent to the border with China. The 21 ethnic groups living alternately created Ha Giang with a vibrant and diverse cultural picture. Implementing the strategy of taking traditional culture as a driving force for tourism development and promoting tourism to preserve culture, over the past time, Ha Giang province has been quite successful in bringing tangible and intangible cultural values to the world, in which there are types of folk art and literature into the model of community-based tourism to serve tourists. This article presents the current status of exploitation, conservation, and unique values of folk art and literature on ethnic minorities in the socio-economic development of Ha Giang province. This article also evaluates the achievements and limitations of several policies that have been implemented in the past. Hence, the solutions proposed to develop policies to exploit and preserve the values of natural resources include folk art and literature of the ethnic minorities in Ha Giang Province appropriately and effectively, contributing to the province's socio-economic development in the current context.